The Effect of C-Reactive Protein Isoforms on Nitric Oxide Production by U937 Monocytes/Macrophages - Sproston, Nicola R.; El Mohtadi, Mohamed; Slevin, Mark; Gilmore, William; Ashworth, Jason J. (Frontiers in Immunology, 2018)
Inflammation is regulated by many endogenous factors including estrogen, a steroid hormone that declines with increasing age, leading to excessive inflammation in the elderly. C-reactive protein (CRP) is an acute phase inflammatory protein that exists in two forms, native CRP (nCRP) and monomeric CRP (mCRP), which mediate distinct biological activities. It is unclear how each CRP isoform mediates nitric oxide (NO), a signalling molecule generated by NO synthase (NOS). This study investigated whether CRP isoforms have distinct effects on NO production by unstimulated and lipopolysaccharide (LPS)-activated monocytes/macrophages and whether estrogen mediates CRP-induced NO production in an in vitro model of ageing. NO and inducible NOS (iNOS) were measured (n=12) by the Griess assay and an enzyme-linked immunosorbent assay (ELISA) respectively following incubation (24 hours) of human-derived U937 monocytes/macrophages with CRP isoforms ([nCRP] = 500 and 1000µg/ml; [mCRP] = 100 and 250µg/ml) in the absence or presence of 17 beta-estradiol (1x10-7, 1x10-8 and 1x10-9M). The response to each CRP isoform and estrogen was dependent on the differentiation and activation status of cells. Monocytes with or without prior LPS-activation significantly increased (P<0.01) NO/iNOS production when treated with mCRP. The mCRP isoform had no effect (P>0.05) on NO/iNOS production by unactivated or LPS-activated macrophages whereas nCRP significantly (P<0.05) reduced NO/iNOS production by macrophages, with or without prior LPS-activation. The nCRP isoform had opposing actions on monocytes, significantly (p<0.01) increasing and reducing NO/iNOS by unactivated and LPS-activated monocytes respectively. Estrogen significantly (P<0.01) reversed nCRP-mediated NO inhibition by unactivated macrophages but decreased CRP-induced NO by unactivated monocytes treated with nCRP or mCRP and LPS-activated monocytes treated with mCRP. NO was differentially mediated by CRP isoforms in a cell-type/state specific manner, with production corresponding to concomitant changes in iNOS levels. Collectively, the findings indicate nCRP and estrogen predominantly reduce NO production whereas mCRP increases NO production. This supports growing evidence that mCRP exacerbates inflammation whilst nCRP and estrogen dampen the overall inflammatory response. Therapeutic strategies that restore estrogen levels to those found in youth and promote the stability of nCRP or/and prevent the formation of mCRP may reduce NO production in age-related inflammatory conditions.